Vineyard Management and Its Impacts on Soil Biodiversity, Functions, and Ecosystem Services - Giffard, Brice; Winter, Silvia; Guidoni, Silvia; Nicolai, Annegret; Castaldini, Maurizio; Cluzeau, Daniel; Coll, Patrice; Cortet, Jérôme; Le Cadre, Edith; d’Errico, Giada; Forneck, Astrid; Gagnarli, Elena; et al. (Frontiers in Ecology and Evolution, 2022)
Healthy soils form the basis of sustainable viticulture, where soil characteristics have a direct impact on wine quantity and quality. Soil not only provides water and nutrients to vines, but is also a living medium containing micro- and macroorganisms that perform many ecological functions and provide ecosystem services. These organisms are involved in many processes, from decomposing organic matter to providing minerals to vine roots. They also control diseases, pests, and weeds, in addition to improving the soil structure in terms of its capacity to retain water and nutrients. Related to decomposition processes, the carbon content of vineyard soils influences fertility, erosion and biogeochemical cycles, with significant implications for the global climate. However, common agricultural practices represent strong threats to biodiversity and associated ecosystem services provided by vineyard soils. As consumers increasingly consider environmental aspects in their purchase decisions, winegrowers have to adapt their vineyard management strategies, raising the demand for sustainable pest- and weed-control methods. This article presents a comprehensive review of the impacts of vineyard practices on the soil ecosystem, biodiversity, and biodiversity-based ecosystem services, and provides future prospects for sustainable viticulture.